Case of non-alcoholic Wernicke's encephalopathy. Issue 11 (14th November 2019) - Theodoreson, Mark D; Zykaite, Ausrine; Haley, Michael; Meena, Saroj
Abstract : A 61-year-old obese man presented with 8-week history of nausea and occasional vomiting. He reported poor appetite and unintentional weight loss of more than 20 kg of his body mass. A week after admission, he developed double vision and unsteady gait. Neurological examination revealed isolated sixth cranial nerve palsy on the left side with horizontal nystagmus that progressed to bilateral lateral gaze palsy with normal vertical gaze. Brain MR revealed T2/fluid attenuation inversion recovery (FLAIR) high signal in mammillary bodies, tectum of the midbrain and the periaqueductal grey matter. He was diagnosed with Wernicke's encephalopathy (WE). WE is a medical emergency that carries high mortality yet can be often under-diagnosed in the non-alcoholic patient. Varied presentation and absence of alcohol dependence lowers the degree of suspicion and this was true in this case. The patient was given intravenous thiamine and made a rapid and dramatic recovery.